Mental Illness as The Other and Hope in Selected Lyrics by TOMORROW X TOGETHER - Alif Akmal Abdul Majid (J-Lalite: Journal of English Studies, 2022)
This article is a thematic analysis of selected song lyrics by Korean pop boy band, TOMORROW X TOGETHER. TOMORROW X TOGETHER is known for their profound and relatable lyrics that appeal to young people particularly when it comes to mental health issues. Mental illness is regarded as uncommon, and individuals suffering from it are being identified as the “Other” by society. This paper will analyze three of TOMORROW X TOGETHER’s song lyrics from their repackaged album, The Chaos Chapter: Fight or Escape (2021) namely Loser=Lover, Anti-Romantic, and 0X1=Lovesong (I Know I Love You). This article aims to examine the themes of mental illness as the Other and hope that can be found in the lyrics of the songs. In addition, the narrative exploration reveals a link between the three songs, revealing a persona that is facing depression and anxiety while seeking to find hope in life, illustrating the misconception of complete powerlessness